(3QSGdI aj GdChaGb oeaUdIs ((3oeUWai Hf jhfS s)
(3ChdgG (B:s
(3hHYO agPG eG GSJaOfG ef TjNfG GdSjO SdjeGf CafOj RGOg hgj bhGYO GdChaGb s
(3BNQgG (B:s
(3hGfbU ef gPG GdYOO JSJhj ajg GdCYOGO bdjdI cGfJ Ch cKjQI hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B- (3HZOGO (B(453) s
Keywords: (3GdMQha h GdChaGbs